Blending Pilgrimage and Learning or the Literary Genres of Riḥla and Muʿjam: Al-Tujībī’s Travelogue to Egypt and Ḥijāz - Midilli, Muhammet Enes (Religions, 2025)
From the early centuries of Muslim history, one of the most popular pilgrimage routes for the Andalusian and Maghribī pilgrims involved traveling through Alexandria to Cairo, then onward to Upper Egypt, followed by a sea journey to Jidda and finally reaching Makka. In the thirteenth and fourteenth centuries, several Maghribī scholars followed this route, combining the pilgrimage journey with scholarly pursuits. Among them, al-Qāsim b. Yūsuf al-Tujībī (d. 730/1329) compiled a travelogue titled Mustafād al-Riḥla wa-l-Ightirāb (The Benefits of Travel and Being Abroad), in which he blended the literary genres of riḥla (travelogue) and muʿjam al-shuyūkh (biographical dictionary of one’s teachers). This article spatializes al-Tujībī’s journey, as depicted in Mustafād al-Riḥla, by employing geographical information systems software to map the locations and routes described in his travelogue. Additionally, the paper examines the structure and style of the travelogue, which blends the riḥla and muʿjam genres, highlighting the combination and hybridization of literary forms. This analysis considers al-Tujībī’s engagement with encyclopedic compilations in Mamluk Cairo and the influence of this intellectual environment on his work. Finally, by highlighting the scholarly network that al-Tujībī established in Egypt and Ḥijāẓ, the paper explores the role of pilgrimage journeys in merging religious duty with scholarly pursuits.